A revision of the Maechidiini Burmeister, 1855 (Coleoptera: Scarabaeidae: Melolonthinae) from the Indo-Australian transition zone, and the first record of the tribe west of Wallace’s Line - Telnov, Dmitry (European Journal of Taxonomy, 2020)
Features of the Maechidiini (Scarabaeidae: Melolonthinae) genera Maechidius Macleay, 1819, Epholcis Waterhouse, 1875 and Paramaechidius Frey, 1969 are critically revised and a new synonymy is proposed: Maechidius = Epholcis syn. nov. = Paramaechidius syn. nov. A key to and an annotated checklist of Maechidiini from the Indo-Australian transition zone are presented for the first time. Thirty-five new species are described, namely Maechidius aiyura sp. nov., M. alesbezdeki sp. nov., M. awu sp. nov., M. babyrousa sp. nov., M. bintang sp. nov., M. boessnecki sp. nov., M. brocki sp. nov., M. caperatus sp. nov., M. ciliatus sp. nov., M. crypticus sp. nov., M. dani sp. nov., M. deltouri sp. nov., M. dendrolagus sp. nov., M. hamatus sp. nov., M. kazantsevi sp. nov., M. konjo sp. nov., M. lapsus sp. nov., M. legalovi sp. nov., M. leucopsar sp. nov., M. longipes sp. nov., M. mailu sp. nov., M. maleo sp. nov., M. merdeka sp. nov., M. miklouhomaclayi sp. nov., M. nepenthephilus sp. nov., M. owenstanleyi sp. nov., M. riedeli sp. nov., M. similis sp. nov., M. skalei sp. nov., M. sougb sp. nov., M. suwawa sp. nov., M. trivialis sp. nov., M. ursus sp. nov., M. weigeli sp. nov. and M. yamdena sp. nov. Six new synonyms are proposed: Maechidius Macleay, 1819 = Epholcis Waterhouse, 1875 syn. nov. = Paramaechidius Frey, 1969 syn. nov., Maechidius esau Heller, 1914 = M. setosus Moser, 1920 syn. nov. = M. setosellus Frey, 1969 syn. nov., Maechidius heterosquamosus Heller, 1910 comb. rest. = Paramaechidius clypeatus Frey, 1969 syn. nov. and Maechidius paupianus Heller, 1910 = M. arrowi Frey, 1969 syn. nov. The first records of Maechidiini from the Tanimbar Islands (Yamdena), Sangihe Islands (Sangir) and Lesser Sunda Islands (Bali) are documented, of which the latter two are the northern- and westernmost known records of Maechidius and of the tribe Maechidiini. Lectotypes are designated for 23 species. Fifteen new combinations are proposed and the original combination to Maechidius is restored for four species. Ecological data are presented for the first time for selected Papuan and Wallacean species. Type material of Wallacean and Papuan Maechidiini is depicted for the first time. A key to species is given. In total, 78 species of Maechidiini are confirmed for the Indo-Australian transition zone.